FRI0566 Attributes of The Subcutaneous Biologic Therapy Preferred by Patients with Rheumatic Disease and Satisfaction with The Treatment. RHEU LIFE Survey. (15th July 2016) - González, C.M.; Carmona, L.; de Toro, F.J.; Arteaga, M.J.; Fernández, S.; Cea-Calvo, L.; Batlle, E.
Abstract : Background: Preferences of patients and satisfaction with the medication are important to improve adherence and outcomes. Objectives: In patients with rheumatoid arthritis (RA), axial spondyloarthritis (SpA) and psoriatic arthritis (PsA), we explored the attributes of drugs preferred by them, and the degree of satisfaction with the current medication. Methods: RHEU-LIFE was a survey to patients >18 years-old with RA axial SpA or PsA treated with subcutaneous (SC) biological drugs, from 50 outpatient rheumatology hospital clinics. Patients responded anonymously to the survey. They ranked 5 treatment attributes from 1 (the most important) to 5 (the least important), and expressed their satisfaction with each one from "very satisfied" to "very dissatisfied". Results: The survey was given to 1000 patients, 592 responded (59.2%, mean age 51.7 years, 42.4% men and 57.6% women; underlying disease RA: 304 (54.2%), axial SpA: 141 (25.1%), PsA: 116 (20.7%), not identified: 31. The biological drug was first (60.4%), second (26.8%) and third or more (13.5%). The attributes mentioned most frequently as "the most important" were normalization of quality of life (QoL) and symptoms control (43.6% and 32.5%, table). The importance was similar in patients with different diseases or treated with first, second or third biologic. The percentage "satisfied" or "very satisfied" was high for every attribute (80% or higher, table) and similar between patients with different conditions. The percentage "satisfied" or "very satisfied" with symptoms control and normalization of QoL was greater in those receiving the first biologic (87.8% and 85.7%) and lower with the third or more (78.4% and 72.0%, both p<0.05). No differences were found for the rest of the attributes. Conclusions: Patients with rheumatic diseases treated with SC biological drugs give more importance to normalization of the quality of life and symptom control than to tolerability, speed of action and the comfort or easeness of use, and express a high degree of satisfaction with their current treatment, especially those receiving therapy with a first biologic. Acknowledgement: Financed by Merck Sharp & Dohme of Spain and endorsed by the patients' association ConArtritis (Arthritis National Coordinator). Disclosure of Interest: None declared